Análisis financiero y su impacto en la toma de decisiones de la empresa Fraven s.a, cantón Ventanas, año 2014 - Solórzano Suárez, Yajaira Gabriela (2016)
The research project called financial analysis and its impact on decision making of the company FRAVEN SA, Canton Ventanas, 2014, is that it can understand fully the use of the financial analysis, which starts with an internal diagnosis and external, to find out the reality in which the company is located. The main objective is to conduct financial analysis to help managers make sound decisions about appropriate funding, and thus determine the future of investments in the organization. The project aims to become an effective tool for the company to renew the way of making decisions, so it is necessary to introduce and implement the financial statements, and the performance of each of the workers who determines and defines the fields of action each put increasing employee efficiency and indicated what they should do in order to improve the functioning of the organization. Have timely and relevant financial information can build a firm foundation for better decision making. To carry out the methodological part different methods as were used: observation, inductive and deductive, an interview was conducted the manager in order to know the company, the investigation was no statistical formulas was applied considering it is a finite universe. A non-experimental design was used because the investigation was based on observation. Illustration of financial analysis of the company, identifying strategies used in decision making, identification of strategies to obtain competitive advantages of the company: In this research project includes a study develops.